2010
DOI: 10.1007/978-3-642-12334-4_23
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal View of HTTP Traffic

Abstract: Abstract.In this paper we analyze three and a half years of HTTP traffic observed at a small research institute to characterize the evolution of various facets of web operation. While our dataset is modest in terms of user population, it is unique in its temporal breadth. We leverage the longitudinal data to study various characteristics of the traffic, from client and server behavior to object and connection characteristics. In addition, we assess how the delivery of content is structured across our datasets,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…While the server needs to support HTTP/1.1 for persistent and pipelined request, the browser ultimately has to issue the request. Callahan et al [2] observed a drastic change in the number of requests per connection and attributes the change to a different default browser version in the environment they monitor.…”
Section: Impact Of Browsermentioning
confidence: 99%
“…While the server needs to support HTTP/1.1 for persistent and pipelined request, the browser ultimately has to issue the request. Callahan et al [2] observed a drastic change in the number of requests per connection and attributes the change to a different default browser version in the environment they monitor.…”
Section: Impact Of Browsermentioning
confidence: 99%
“…Studies are based on aggregated traffic captured at internet hubs or large organizations (e.g., universities) access links. These studies expose general trends in HTTP usage and workload [5], [2], or focus on some particular Web 2.0 applications such as interactive maps. [6], [7], [8], [9], [10] Our work comes as a complement, by providing a fine-grained study of the various Web applications.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, we considered measuring median and average HTTP object download times, but find that latency is a reliable predictor for such times. (During preliminary testing we discovered that round-trip-time correlates to download time for a median-sized-400-byte [17]-object with a Pearson correlation coefficient of approximately 0.83, for both a default path as well as a poisoned path that affected 30% of the replica clients.) Hence, we measure three basic network performance primitives: latency, throughput, and jitter.…”
Section: Measuring Performance Improvementsmentioning
confidence: 98%
“…Google research showed that a 500-millisecond increase in latency caused a 20% traffic drop [8], while it was reported that a latency increase of 100 milliseconds can produce a 1% drop in revenue for Amazon [28]. Accordingly, recent years have seen many optimizations to accelerate the delivery of such services, ranging from better transport protocols [40] to browser enhancements [4,7] to new compression and site optimization algorithms [1,17].…”
Section: Introductionmentioning
confidence: 99%